Urban Security Governance in Residential Neighbourhoods: A Researcher’s Perspective - Balogun, Femi Adekunle (Southern African Journal of Security)
This article reviews studies on urban security governance in residential neighbourhoods with a view to improving the integrated security system in the residential neighbourhoods of cities in Africa and beyond. One of the social problems facing the globe, most especially in African nations, is insecurity, which varies from kidnapping to banditry, armed robbery, killings, bombing attacks, killer herdsmen, insurgency, militancy, Boko Haram and Jihadism. Urban security governance is emerging as an alternative framework to address the inability of state institutions to provide adequate security in towns and cities. Concepts of urban security governance and the broken windows theory, securitization, collective security, security governance, and citizens’ participation provided the framework for the current study, while the systemic review of the literature was adopted as the methodology. Secondary desk data on urban security governance in residential neighbourhoods was used as the basis for explanation. The study revealed that the inability of the state to provide adequate protection made individuals, communities and businesses engage in different urban security approaches. Issues of weakness in urban security governance have resulted in the emergence of insecurity in residential neighbourhood areas. However, institutionalising urban security governance through the adoption of an integrated security system approach in residential neighbourhoods is highly recommended.